Violence against Women and Ethnicity: Commonalities and Differences across Europe - Schröttle, Monika; Thiara, Ravi K.; Condon, Stephanie A. (Verlag Barbara Budrich, 2011)
This book draws together both: theory and practice on minority/migrant women and gendered violence. The interplay of gender, ethnicity, religion, class, generation and sexuality in shaping the lives, experiences and choices of minority/migrant women affected by violence has not always been adequately theorised within much of the existing writing on violence against women. Feminist theory, especially the insights provided by the concept of intersectionality, are central to the editors' conceptual frameworks.